(untitled) (Research, Society and Development, 2021)
This study aims to analyze the spatial autocorrelation of limb amputations and amputation incidence rates among the municipalities of Alagoas. An ecological study with data from the SUS Department of Informatics, the units of analysis were the municipalities and the amputation rate. Limb amputation cases registered between 2007-2018 were included. The incidence rate was smoothed by the local Bayesian method and the Moran index was used for spatial dependence analysis in TerraView and thematic maps edited in QGis. Spearman correlation and simple regression model compared rates with regional socioeconomic indicators. 9345 amputation records notified in the state. The Bayesian estimate smoothed areas and discriminated heterogeneity with more municipalities with high rates and areas of epidemiological transition. Moran’s spatial analysis exhibited quadrennial (2007-2010) global index value 0.133385, (2011-2014) 0.215665, (2015-2018) 0.276478 foreshadowing evidence of positive spatial autocorrelation. The univariate regression analysis showed the amputation incidence rate related to indicators that reflect the population’s vulnerable life situation, the unemployment rate (11.4%), per capita income (8.5%) and male illiteracy rate (12.9%) percentages of explanation. The spatial distribution of amputations showed a non-homogeneous distribution pattern with agglomerations in the agreste and eastern regions of Alagoas. They are the ones who feel the impact of inequalities in income distribution, education conditions and difficulty in accessing health services the most. Understanding the geographic growth of CNCDs reveals them as a critical point in public health.